Literature and Its Teaching... a Second Call - Guillermo Bustamante Zamudio (Universidad Pedagógica Nacional, 2016)
Like any social issue, education is subject to explanations. However, not all of them have the same level of development, and the political way usually imposes one temporarily, which deprives it of any conceptual legitimacy. Given the human condition, the regulative is a constituent element of education, not something imposed to education, and deletable on behalf of its frequent excesses. Thus, the teaching of literature cannot evade its regulatory dimension, even though some believe it is an issue of unconditional freedom, while its production and consumption require restrictions. Access to literature is not free and spontaneous. Creating conditions of possibility does not always meet what students want "naturally". In this sense, this subject is not different from others, and its instructional dimension is related to the specificity of the school.